A Wideband Circularly Polarized Dielectric Resonator Antenna Using Inverse f-Shaped Slot Excitation with Parasitic Metal Structure. (2nd August 2022) - Chen, Zizu; Yu, Guoliang; Wu, Di; Zhu, Mingmin; Qiu, Yang; Zhou, Hao-Miao
Abstract : In this paper, a single-fed wideband circularly polarized dielectric resonator antenna (DRA) is proposed. The antenna consists of a substrate, a cylindrical dielectric resonator, and four curved parasitic metal blocks that are rotated and placed around the dielectric resonator. The GND of the substrate is etched with an inverse f -shaped slot. The orthogonal working mode of the DRA is excited by the inverse f -shaped slot coupled to the microstrip, thereby obtaining circularly polarized radiation. The impedance bandwidth and axial ratio bandwidth of the antenna are improved by optimizing the structure of the inverse f -shaped slot and the shape and size of curved parasitic metal blocks, and finally, a circularly polarized dielectric resonator antenna with significant bandwidth advantages is obtained. The antenna is simulated, fabricated, and measured. The measured results show that the proposed circularly polarized DRA has an impedance bandwidth of 58.5% (2.61–4.77 GHz) and an axial bandwidth of 55.2% (2.75–4.85 GHz) and finally achieves an effective axial bandwidth of 53.7% (2.75–4.77 GHz), the peak gain of 6.84 dBi, and average efficiency of 90.78%, with excellent overall performance.